Role of SiOx interlayer in the electrochemical degradation of Amaranth dye using SS/PbO2 anodes. (15th November 2016) - Elaissaoui, Ines; Akrout, Hanene; Grassini, Sabrina; Fulginiti, Daniele; Bousselmi, Latifa
Abstract: A novel SS (Stainless steel)/SiOx /PbO2 anode for dye removal in water electrolysis was studied. SiOx interlayer was deposited by plasma enhanced chemical vapor deposition (PECVD) in plasma fed with argon, oxygen and tetraethoxysilane (TEOS) in different ratios. Lead oxide was deposited by pulsed electrodeposition. Well-adherent and homogeneous SiOx film, characterized by high hydrophobicity, were deposited in oxygen rich plasma onto the SS substrate as confirmed by the morphological characterization performed by means of Field Emission Scanning Electron Microscopy (FESEM). The composition of PbO2 layer was investigated by X-ray diffractometry (XRD) and evidenced that β-PbO2 crystallites nucleation was promoted by the SiOx interlayer. Additionally, Electrochemical Impedance Spectroscopy (EIS) measurements were performed for assessing the electrochemical behaviour of the SS/SiOx /PbO2 anodes. Results confirmed that the increase in the presence of the β-PbO2 form, increases the conductivity of the PbO2 film. Finally, the anode, with SiOx interlayer deposited in oxygen rich plasma, showed the best efficiency in removing the azoic dye from aqueous solution in terms of COD and color removal. Graphical abstract: Highlights: A larger amount of oxygen in SiOx interlayer induces a better nucleation of the β-PbO2 form. The hydrophobic character of PbO2 surface is related to the fraction of oxygen used to deposit SiOx interlayer. Remarkable degradation ability of PbO2 electrode with inorganic SiOx interlayer.